2009
DOI: 10.1111/j.1755-3768.2008.01251.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of habitual refractive errors and anisometropia among Dutch schoolchildren and hospital employees

Abstract: ABSTRACT.Purpose: Refractive error (RE) is suggested to cause not only visual impairment, but also functional problems such as aspecific health complaints and lower levels of school achievement. During the last few decades the prevalence of myopia has increased worldwide, especially in Asia. We investigated the prevalence of habitual RE and anisometropia in a Dutch population of children and employees. Methods: In a cross-sectional study, RE in both eyes of 520 children (aged 11-13 years) and 444 hospital empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
(28 reference statements)
2
15
1
Order By: Relevance
“…It has been reported a prevalence of myopia of 11.6% for children aged 5 to 17 years and 20% for children aged 12 years and increased to 33% for those aged ≥ 20 years (46)(47)(48), and in study on 2353 Austeralian students aged 11-15-years old, the prevalence of myopia was 4.6% and this amount was 6.1% among European Caucasian and Middle Eastern children respectively, whereas prevalence of myopia was 31.5% among South Asian children (49). Similar to our findings, the increasing prevalence of myopia with age was observed in the population-based studies in some countries such as Taiwan (5), Australia (6), Singapore (7), Malaysia (13), and Indonesia (50). The prevalence of myopia and high myopia in our study was 66.2% and 4.65%, respectively, which significantly increased with age (from 32.96% in 7-yearold children to 79.02 in 18-year-old ones).…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported a prevalence of myopia of 11.6% for children aged 5 to 17 years and 20% for children aged 12 years and increased to 33% for those aged ≥ 20 years (46)(47)(48), and in study on 2353 Austeralian students aged 11-15-years old, the prevalence of myopia was 4.6% and this amount was 6.1% among European Caucasian and Middle Eastern children respectively, whereas prevalence of myopia was 31.5% among South Asian children (49). Similar to our findings, the increasing prevalence of myopia with age was observed in the population-based studies in some countries such as Taiwan (5), Australia (6), Singapore (7), Malaysia (13), and Indonesia (50). The prevalence of myopia and high myopia in our study was 66.2% and 4.65%, respectively, which significantly increased with age (from 32.96% in 7-yearold children to 79.02 in 18-year-old ones).…”
Section: Discussionsupporting
confidence: 79%
“…Several studies have found an increased prevalence as a function of age in the teenage years apparently mirroring the increase in myopia prevalence (e.g. Hirsch, 1967; Hendricks et al, 2009; Lin et al, 1999; but see Czepita et al, 2005). …”
Section: Prevalencementioning
confidence: 97%
“…6,7 Anisometropia, the difference in the refractive errors between the eyes, is believed to be an important factor for developing amblyopia. Habitual anisometropia with more than 1.00 D was reported to be common; 8 however, high anisometropia is rare. High degrees of anisometropia cause disparity in image size between the two eyes of anisometropia (aniseikonia) and it has traditionally been believed that anisometropia of more than 3.5 D inhibits fusion.…”
Section: Introductionmentioning
confidence: 97%